Legal support of social entrepreneurship in the Republic of Kazakhstan - Zhumadilov А.К.; Maishekina Э.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article examines important issues of the application of legal support for social entrepreneurship in the Republic of Kazakhstan, especially the constitutional and administrative norms of legal regulation of social entrepreneurship in the Republic of Kazakhstan. The issues of constitutional and administrative regulation concern the following significant problems, in particular: the concept of legal support for social entrepreneurship in the Republic of Kazakhstan, in particular, the study of its content and system. It is important to study the legal relations within the legal support of social entrepreneurship in the Republic of Kazakhstan. The article reflects the discussion of a number of prominent scientists on the problem of the implementation of legal support for social entrepreneurship in the Republic of Kazakhstan. A special place is occupied by the issue of the application of constitutional and administrative norms in the regulation of the legal support of social entrepreneurship in the Republic of Kazakhstan, the content of the application of entrepreneurial legislation in general. It should be pointed out that the main goal of state policy in this area should be to create conditions for effective legal support of social entrepreneurship in the Republic of Kazakhstan and the prevention of its violation. It is not enough to consolidate the right in legislation. The implementation of legal regulation of social entrepreneurship in the Republic of Kazakhstan depends on many factors, including non-legal nature, however, the more economic issues are regulated by law, the easier it will be for individuals to exercise their right. Legal support of social entrepreneurship in the Republic of Kazakhstan requires uniformity and subordination to common goals not only of the norms of constitutional law, but also of other branches. For the legal support of social entrepreneurship, one of the priorities should be to streamline the legal regulation of the sphere of entrepreneurship as a whole, since without this, neither the implementation of this mechanism nor its protection is possible.